2020
DOI: 10.1093/plcell/koaa018
|View full text |Cite|
|
Sign up to set email alerts
|

Gain-of-function of the 1-aminocyclopropane-1-carboxylate synthase geneACS1Ginduces female flower development in cucumber gynoecy

Abstract: Unisexual flowers provide a useful system for studying plant sex determination. In cucumber (Cucumis sativus L.), three major Mendelian loci control unisexual flower development, Female (F), androecious [a; 1-aminocyclopropane-1-carboxylate {ACC} synthase 11, acs11], and Monoecious (M; ACS2), referred to here as the Female, Androecious, Monoecious (FAM) model, in combination with two genes, gynoecious (g, the WIP family C2H2 zinc finger transcription factor gene WIP1) and the ethylene biosynthetic gene ACC oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 38 publications
0
31
0
Order By: Relevance
“…We next performed genome-wide association studies (GWAS) using these genotyped SVs for three traits: female flower rate on a primary branch, fruit spine/wart density, and branch number. Two reported genes involved in cucumber sex determination ( m 30 and F 31 , 32 ) were detected in our association signals (Supplementary Fig. 7a ), and the highest peak of fruit spine/wart density on chromosome 6 directly pinpointed the reported causative SV (SV_COMINS_6G012210) upstream of CsGL3 (ref.…”
Section: Resultsmentioning
confidence: 63%
“…We next performed genome-wide association studies (GWAS) using these genotyped SVs for three traits: female flower rate on a primary branch, fruit spine/wart density, and branch number. Two reported genes involved in cucumber sex determination ( m 30 and F 31 , 32 ) were detected in our association signals (Supplementary Fig. 7a ), and the highest peak of fruit spine/wart density on chromosome 6 directly pinpointed the reported causative SV (SV_COMINS_6G012210) upstream of CsGL3 (ref.…”
Section: Resultsmentioning
confidence: 63%
“…These results indicated that the antagonistic relationship between CsWIP1 expression and ethylene synthesis was still present in exogenous auxin-induced cucumber sex determination. Because the mutation in CsACO2 (in the 406a line) results in the inhibition of ethylene synthesis in sex determination [ 12 , 15 ], the 406a line was used to determine the direct effect of exogenous IAA on sex-controlling genes. At 1 h of IAA treatment, CsACS2 and CsACS11 were upregulated, and the upregulation of CsACS2 was greater than that of CsACS11 .…”
Section: Discussionmentioning
confidence: 99%
“…In cucumber, CsACS2 and CsACS11 encode ACC synthases with different functions in sex determination. The ethylene synthesized jointly by CsACS11 and CsACO2 can promote the expression of CsACS2 , which then inhibits stamen development [ 12 , 17 ]. Mutations in CsACS2 and CsACS11 lead to the emergence of andromonoecious and androecious plants, respectively [ 14 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations